Surgical management of chronic hyperplastic candidiasis refractory to systemic antifungal treatment - Shah, Neha; Ray, Jay Gopal; Kundu, Sanchita; Sardana, Divesh (Journal of Laboratory Physicians, 2017)
Chronic hyperplastic candidiasis (CHC), earlier known as candidal leukoplakia, is a variant of oral candidiasis that classically presents as a white patch on the commissures of the oral mucosa and it is mostly caused by Candida albicans. Clinically, the lesions are usually asymptomatic and regress after appropriate antifungal therapy and correction of the underlying cause. If the lesions are untreated, a small portion may develop dysplasia and later progress into carcinoma. The purpose of this article is to report a case of CHC in a 57-year-old male patient with a significant smoking habit, who presented with a thick, nonscrapable, brownish-white coating on the dorsum of the tongue for 9 years. This case is of particular importance and concern because of the high risk for malignant transformation in CHC. The role of biopsy and histopathology is also stressed through this case report in arriving at a definitive diagnosis and treatment planning. Further, this case is interesting because it was refractory to local and systemic antifungal treatment and so, surgery was chosen as an alternative treatment modality considering the side effects of the prolonged use of antifungal drugs.
Keywords: Chronic hyperplastic candidiasis; malignant transformation; oral candidiasis; smoking; tongue